Impact of COVID-19 on the Risk of Development of Oligohydramnios in Pregnancy: A Retrospective Observational Study - Ipek Ulu; Aytaj Jafarzade; Muhittin Tamer Mungan; Aydan Biri (Journal of Clinical and Diagnostic Research, 2024)
Introduction: The Coronavirus Disease-2019 pandemic is considered the most catastrophic disease of the last decades, with evolving knowledge and improved management over time. Pregnant women are known to be particularly vulnerable, and COVID-19 has been shown to damage the endothelium due to its proinflammatory nature. Aim: To determine the occurrence of oligohydramnios in pregnant women who tested positive for COVID-19. Materials and Methods: A retrospective observational study was conducted at the Department of Obstetrics and Gynaecology, Koru Health Groups, Ankara, Çankaya, Turkey from January 2023 to June 2023. The study included a total of 459 women who were followed during pregnancy and delivered in the same hospital between April 2020 and October 2022. The patients were divided into two groups: COVID-19 positive group (n=101) and negative group (n=358). Various parameters such as age, parity, gestational week at birth, Body Mass Index (BMI), 1st and 5th-minute Appearance, Pulse, Grimace, Activity and Respiration (APGAR) scores, weight of the newborn, Amniotic Fluid Index (AFI), and the risk of developing oligohydramnios were assessed between the positive and negative groups. Parametric variables were analysed using independent t-tests and non parametric ones using Mann-Whitney U tests. Chi-square test was used to compare categorical variables. A p-value of <0.05 was considered statistically significant. Results: The mean age of the pregnant women was 29.2±4.4 years, ranging from 20 to 43 years. Oligohydramnios was detected in 95 women, with 64 of them testing positive for COVID-19. There were no statistically significant differences in terms of age, parity, gestational week of birth, weight at birth, and 1st and 5th-minute APGAR scores between the two groups. However, BMI was significantly higher in COVID-19 positive patients compared to negative ones (p=0.003). Oligohydramnios was found to be significantly higher in COVID-19-positive pregnant women (n=64) compared to negative ones (n=31) (p<0.0001). Conclusion: The COVID-19 pandemic has caused an unprecedented level of global health problems. The virus’s prothrombotic tendency leads to placental insufficiency, predisposing to oligohydramnios and intrauterine growth retardation.